2011
DOI: 10.1116/1.3534023
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition grown metal-insulator-metal capacitors with RuO2 electrodes and Al-doped rutile TiO2 dielectric layer

Abstract: Articles you may be interested inTEMAZ/O3 atomic layer deposition process with doubled growth rate and optimized interface properties in metal-insulator-metal capacitors J. Vac. Sci. Technol. A 31, 01A123 (2013); 10.1116/1.4766281 Improvement in the leakage current characteristic of metal-insulator-metal capacitor by adopting RuO2 film as bottom electrode Appl. Phys. Lett. 99, 022901 (2011); 10.1063/1.3609875 Influence of precursor chemistry and growth temperature on the electrical properties of SrTiO 3 -based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…These conclusions by Kim et al [551,552,554] are supported for example by the results of Hudec et al who detected Al on the film surface for a 20-nm thick film doped only in its bottom 2.5-nm part; the through-thickness Al concentration was far from constant though [130]. Apart from the higherthan-average Al content on the top surface, the depth profile of the Al concentration may also exhibit a peak at the film-substrate interface [130]. Furthermore, from XPS investigation it has been shown that Al ions form in rutile-structured films a chemically uniform Al-Ti-O film without any phase separation [551]; also, for anatase films peak shifts in Raman data have indicated that Al 3+ substitutes for Ti 4+ in the anatase lattice [650].…”
Section: Al Dopingmentioning
confidence: 78%
See 2 more Smart Citations
“…These conclusions by Kim et al [551,552,554] are supported for example by the results of Hudec et al who detected Al on the film surface for a 20-nm thick film doped only in its bottom 2.5-nm part; the through-thickness Al concentration was far from constant though [130]. Apart from the higherthan-average Al content on the top surface, the depth profile of the Al concentration may also exhibit a peak at the film-substrate interface [130]. Furthermore, from XPS investigation it has been shown that Al ions form in rutile-structured films a chemically uniform Al-Ti-O film without any phase separation [551]; also, for anatase films peak shifts in Raman data have indicated that Al 3+ substitutes for Ti 4+ in the anatase lattice [650].…”
Section: Al Dopingmentioning
confidence: 78%
“…Moreover, first-principle calculations have indicated that Al atoms find energetically favourable positions on the surface of rutile TiO2, such that there is a driving force for Al atoms towards the film surface during the growth [552]. These conclusions by Kim et al [551,552,554] are supported for example by the results of Hudec et al who detected Al on the film surface for a 20-nm thick film doped only in its bottom 2.5-nm part; the through-thickness Al concentration was far from constant though [130]. Apart from the higherthan-average Al content on the top surface, the depth profile of the Al concentration may also exhibit a peak at the film-substrate interface [130].…”
Section: Al Dopingmentioning
confidence: 88%
See 1 more Smart Citation
“…This means that the large difference in capacitance density in Figure 1a was not induced by the change in the bulk properties, including the possible outward diffusion of Al into the RuO 2 electrode. 13 Interestingly, a certain difference (approximately 0.1 nm) in the y-intercept between the Pt and RuO 2 TEs was observed for all the three cases: the capacitors with Pt TE showed a higher EOT than those with RuO 2 TE. This means that the interfacial layer between Pt TE and TiO 2 or ATO has a lower dielectric constant than the interfacial layer between RuO 2 TE and TiO 2 or ATO, which is the main reason for the higher capacitance density of ATO with RuO 2 TE in Figure 1a.…”
Section: ■ Experimental Sectionmentioning
confidence: 88%
“…26,[32][33][34] Among these films, the PECVD Si 3 N 4 is the most widely used, as it can be deposited at 300 C and is compatibility with GaAs processing, with a 60 nm film having good physical, chemical, and electrical characteristics, including a high dielectric breakdown voltage of 65 V and a breakdown field of 10 MV/cm or higher. 1,2 This PECVD Si 3 N 4 film has been used as capacitor dielectric in GaAs HBT, 1,2,35 high electron mobility transistor (HEMT), 36,37 and other monolithic microwave integrated circuits (MMIC) 18,38 technologies.…”
Section: Introductionmentioning
confidence: 99%